(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the role of critical thinking in foreign language lessons in primary school. It examines modern pedagogical approaches that promote analytical and reasoning skills in young learners. The article also highlights the importance of developing critical thinking for successful language acquisition and communication. Furthermore, it discusses strategies for integrating critical thinking into lesson plans and classroom activities. By fostering students’ ability to analyze, evaluate, and create, educators can enhance language proficiency and independent thinking. The study also emphasizes the role of interactive tasks, discussions, and problem-solving exercises in promoting cognitive development. Finally, the article provides recommendations for teachers on how to effectively implement these strategies in their curriculum.